Hamstring strength assessment methods in sport: A systematic review and meta-analysis of post-activity strength decrements, asymmetry benchmarks, and measurement reliability - Adam E. Sundh; Nicholas J. Ripley; A. J. Lamb; Paul Comfort (PLoS ONE, 2026)
Hamstring strain injuries (HSI) represent one of the most prevalent and recurrent injuries in sport, making reliable strength assessment essential for neuromuscular monitoring in athletic populations. Despite the breadth of available testing modalities, no comprehensive synthesis of assessment methods, their reliability, post-activity strength responses, or normative asymmetry values has been undertaken. This systematic review and meta-analysis aims to evaluate the reliability of hamstring strength assessment methods, quantify the time-course of strength decrements following competition, establish normative inter-limb asymmetry benchmarks, and identify gaps to guide future assessment practices. PubMed, Scopus, SPORTDiscus, and Web of Science were searched from inception to November 1, 2025 following PRISMA guidelines. Methodological quality was assessed using a modified version of the Downs and Black checklist. A total of 161 studies were included in qualitative synthesis and 106 in quantitative analysis. Isokinetic dynamometry was the most frequently used modality, followed by force platform assessments and Nordic hamstring-based devices, with a clear upward trend in field-based testing observed after 2010. Multiple modalities demonstrate good reliability, sensitivity to post-activity fatigue, and comparable patterns to detect inter-limb asymmetries, supporting their use across varied applied settings. Hamstring strength deficits persisted for 24–72 hours following on-field activity, identifying a critical vulnerability window during congested schedules. Minor inter-limb asymmetries of approximately 3–4% appear normative and should not be considered clinically meaningful in isolation. Practitioners should establish individualized baselines and integrate routine monitoring with evidence-based recovery strategies to mitigate HSI risk throughout competitive seasons.